The Role of Smart Pharmacy Automation in Improving Medication Safety: A Systematic Review - Shad, Zufi; Nisarad, Mehwish; Maqbool, Tahmina; Khalil, Anamta; Imran, Hadia (Indus Journal of Bioscience Research, 2025)
Background: Medication errors pose significant risks to patient safety, contributing to 5–6% of hospital admissions globally. Traditional pharmacy systems, reliant on manual processes, are prone to errors due to human factors, inefficient workflows, and inadequate technology integration. Smart Pharmacy Automation Systems (SPAS), leveraging IoT, AI, and cloud-based analytics, offer a transformative solution to mitigate these challenges. Objective: This systematic review evaluates the efficacy of SPAS in reducing medication errors, optimizing workflows, and enhancing patient safety by synthesizing evidence from 48 studies (2020–2025). Methods: Following PRISMA guidelines, PubMed and Google Scholar were searched for peer-reviewed studies on SPAS implementation. Inclusion criteria focused on IoT-enabled automation, error reduction, and integration with Electronic Health Records (EHRs). Quality assessment was conducted using PRISMA standards. Results: SPAS demonstrated significant improvements: (1) Error Reduction: Automated dispensing reduced prescription errors by 42.2% and eliminated dispensing errors; (2) Efficiency: Real-time IoT monitoring cut medication expiration rates by ≤0.3% and audit times by 50%; (3) Safety: Integration with EHRs minimized dosing errors and adverse drug interactions. Challenges included interoperability gaps (23% of studies) and cybersecurity risks (18%). Conclusion: SPAS enhances medication safety and operational efficiency but requires standardized protocols, staff training, and robust cybersecurity measures. Future research should address cost-benefit analyses and scalability in low-resource settings.